1990
DOI: 10.1039/p19900003263
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in fragmentation and rearrangement of α-hydroxyimino-phosphinates and -phosphonates. A synthetic approach to acylphosphon- and phosphor-amidates. Crystal structures of methyl (E)-α-hydroxyimino-benzylphenylphosphinate and methyl benzoylphenylphosphonamidate

Abstract: Reaction of methyl benzoylphenylphosphinate 1 with hydroxylamine gave methyl a-hydroxyiminobenzylphenylphosphinate 2 as a mixture of €and Z isomers with the E isomer predominating. Pure ( E ) -2 when heated gave methyl N-benzoylphenylphosphonamidate 3 as the sole product. In contrast, (Z) -2 when heated gave, as a result of fragmentation, mainly methyl hydrogen phenylphosphonate 4 and benzonitrile, together with methyl N-phenylcarbamoylphenylphosphinate 5 as the minor product; the latter results from Beckmann … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Thus, the most unusual feature of the present reaction is the spontaneous departure of the OH at room temperature. This resembles the Beckmann rearrangements we reported recently, , in which the departure of the OH group took place without the customary acid catalysis. In the present case as well as in the Beckmann rearrangements, OMe derivatives reacted much more sluggishly.…”
Section: Resultssupporting
confidence: 88%
“…Thus, the most unusual feature of the present reaction is the spontaneous departure of the OH at room temperature. This resembles the Beckmann rearrangements we reported recently, , in which the departure of the OH group took place without the customary acid catalysis. In the present case as well as in the Beckmann rearrangements, OMe derivatives reacted much more sluggishly.…”
Section: Resultssupporting
confidence: 88%
“…Bond distances and angles are within the range of those reported for related amide and phosphine derivatives. Note, however, that the P-N bond (1.728(2) Å) is longer than that found in PhP(O)(OMe)NHC(O)Ph (1.674 Å) 21 and in (MeO)P(O)(SMe)NHC(O)Me (1.641 Å) 22 and similar to that of Ph 2 P(S)NHC(O)Ph (1.72(1)Å). 23 The P-N-C(13) bond angle (122.3(1)Њ) is more obtuse than the P-C-C angle found in Ph 2 PCH 2 CO 2 Et (113.24Њ) 24 and Ph 2 PCH 2 CO 2 H (110.188Њ).…”
Section: Crystal Structures Of 1 and 12bmentioning
confidence: 69%
“…32, 33 A well known complication of the Beckmann rearrangement is the Beckmann fragmentation, also referred to as the "abnormal" Beckmann reaction. This occurs usually in cases in which the migrating groups have a tendency to form stable carbocations, which split off as such, instead of migrating from the C to N. 33 In a series of previous papers from our laboratory, over the past decade, we have reported that α-hydroxyiminophosphonate diesters, 34 α-hydroxyiminophosphinate, 34 and α-hydroxyiminophosphonamidate 35 monoesters undergo facile Beckmann rearrangement upon heating. In contrast, acidic α-hydroxyiminophosphonate monoesters (e.g.…”
Section: Discussionmentioning
confidence: 99%